Unit three - Governance. [Training/Course material] - Giordano, Mark; Varma, Samyuktha (2009)
This unit provides an introduction to the key concepts, challenges, perspectives and issues associated with the governance of water resources. Section 1 presents an introduction to the specific challenges of managing water and the issues that frame institutional and policy responses to water resource governance. Section 2 introduces local and community scale water governance systems as a way to improve the access, efficiency and distribution of water through the active participation of water users. It uses the case of Irrigation Management Transfer (IMT) to highlight important issues in local water governance. Section 3 evaluates the limitations of local governance and introduces alternative and complementary mechanisms designed to address those limitations by operating at 'higher' scales. It examines how the simultaneous use of governance mechanisms across scales can take advantage of each mechanism's positive attributes while overcoming its limitations. Section 4 examines how factors beyond the water sector including trade policy, increasing appreciation for the environment and urbanisation impact water governance. The section thus highlights how successful water governance requires a broad understanding of not only water but the larger political economy in which water is used.